2021
DOI: 10.1016/j.jid.2020.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility Criteria Related to Hormone Therapy in Acne Clinical Trials: A Systematic Review

Abstract: N, suppresses IL-17-mediated skin inflammation and is genetically associated with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Individuals receiving hormonal therapy were excluded from the study because the use of exogenous hormones in a pivotal trial would represent a confounding variable that could affect the results obtained. Indeed, a recent evaluation of 86 acne studies showed 37 studies (43%) had exclusion criteria associated with hormone therapy …”
mentioning
confidence: 58%
“…Individuals receiving hormonal therapy were excluded from the study because the use of exogenous hormones in a pivotal trial would represent a confounding variable that could affect the results obtained. Indeed, a recent evaluation of 86 acne studies showed 37 studies (43%) had exclusion criteria associated with hormone therapy …”
mentioning
confidence: 58%
“…Clascoterone reduces inflammatory and non-inflammatory facial acne with minimal adverse effects or safety concerns [ 44 ]. While clinical trials for clascoterone, like most acne clinical trials [ 45 ], did not specifically include any transgender participants or document hormone therapy use of its participants, the use of topical antiandrogens in transmasculine patients has been proposed as a targeted treatment for reducing the unwanted testosterone action in the skin [ 46 ]. Future research should examine the safety of topical androgens, including the potential systemic effects of clascoterone on serum testosterone level, as well as their acceptability by transmasculine patients and hormone providers.…”
Section: Treatment Planmentioning
confidence: 99%
“…Estrogens may also play a role in lesion recuperation and anti-inflammatory methods via their complicated interplay with IGF-1 [57][58][59]. According to a standardized evaluation of over 1,000 researches, cases with acne vulgaris were reduced serum estrogen degrees than controls [60]. It indicates that estrogen can also play a role in the acne's pathogenesis [61].…”
Section: Estrogensmentioning
confidence: 99%